Application of Biochar-Based Materials for Effective Pollutant Removal in Wastewater Treatment - Meiyao Han; Ziyang Liu; Shiyue Huang; Huanxing Zhang; Huilin Yang; Yuan Liu; Ke Zhang; Yusheng Zeng (Nanomaterials)
With the growth of the global population and the acceleration of industrialization, the problem of water pollution has become increasingly serious, posing a major threat to the ecosystem and human health. Traditional water treatment technologies make it difficult to cope with complex pollution, so the scientific community is actively exploring new and efficient treatment methods. Biochar (BC), as a low-cost, green carbon-based material, exhibits good adsorption and catalytic properties in water treatment due to its porous structure and abundant active functional groups. However, BC’s pure adsorption or catalytic capacity is limited, and researchers have dramatically enhanced its performance through modification means, such as loading metals or heteroatoms. In this paper, we systematically review the recent applications of BC and its modified materials for water treatment in adsorption, Fenton-like, electrocatalytic, photocatalytic, and sonocatalytic systems, and discuss their adsorption/catalytic mechanisms. However, most of the research in this field is at the laboratory simulation stage and still needs much improvement before it can be applied in large-scale wastewater treatment. This review improves the understanding of the pollutant adsorption/catalytic properties and mechanisms of BC-based materials, analyzes the limitations of the current studies, and investigates future directions.